Scale-Dependent Diversity Patterns in Subalpine Grasslands: Homogenization vs. Complexity - Tsvetelina Terziyska; James Tsakalos; Sándor Bartha; Iva Apostolova; Desislava Sopotlieva (Land)
This study investigates the scale-dependent alpha and beta diversity patterns in the subalpine grasslands of the Central Balkan Mountains following decades of reduced grazing. We examined two distinct vegetation patches: pure grasslands (N-type) and grasslands mixed with dwarf shrubs (V-type), focusing on coarse-scale (among stands) and fine-scale (within stands) heterogeneity. Using micro-quadrat transects and dissimilarity analyses, we assessed the species composition variability and spatial complexity of the two vegetation patches. The results showed that the N-type exhibited higher coarse-scale beta diversity, attributed to fluctuating dominant grass proportions, and lower fine-scale diversity due to competitive exclusion. Conversely, V-type vegetation displayed lower coarse-scale but higher fine-scale diversity, reflecting the heterogeneous spatial matrix created by dwarf-shrub encroachment. Fine-scale spatial complexity, quantified by the compositional diversity of dominants, strongly correlated with species richness and diversity. Two main conclusions emerged: (a) Grazing decline-driven succession toward grass–dwarf shrub mixtures enhanced local diversity while reducing landscape heterogeneity. Conversely, regeneration toward typical dominant grasses diminished local diversity but increased landscape heterogeneity. (b) A balanced fine-scale spatial mixture of dominant species was found to reduce their individual negative impact on other species’ diversity. Effective high-mountain pasture management requires the consideration of scale and local plant co-existence.